High-corrosion-resistance and high-strength solder and preparation method thereof
By combining solder components such as aluminum, aluminum-silicon alloys, copper, etc. and flux components such as chloride and flux compounds in the solder, and using the design of solder wrapped with the flux, the problem of corrosion and insufficient strength of the solder in harsh environments is solved, and the welding effect with high corrosion resistance and high strength is achieved.
Patent Information
- Application Number
- CN202510134029.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-07
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2045-02-07
AI Technical Summary
Existing solder is prone to corrosion in harsh environments such as high temperature, high humidity, strong acid and alkali, resulting in failure of solder joints and insufficient strength to meet the needs of certain structures.
By combining the solder and the flux, the solder uses aluminum, aluminum-silicon alloys, copper and other components, and chloride and fluoride are used in the flux to form high corrosion resistance and high-strength solder. The structural design of the solder encapsulates the flux to ensure uniform release of the flux.
It significantly improves the strength, corrosion resistance and stability of the welded joints, is suitable for high-performance welding needs, and maintains good performance in harsh environments.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of welding, and in particular to a high-corrosion-resistant and high-strength solder and a preparation method thereof. Background Art
[0002] In the field of modern industrial manufacturing, welding, as a key connection technology, is widely used in many industries such as aerospace, automobile manufacturing, electronic equipment, mechanical engineering, etc. As the requirements for product performance in various industries continue to increase, the performance of solders has also been more stringently challenged, and high corrosion resistance and high strength solders have become the focus of research and development.
[0003] Traditional solders have many deficiencies in terms of corrosion resistance and strength. In many application scenarios, especially in harsh working environments such as high temperature, high humidity, strong acid and alkali conditions, ordinary solders are easily corroded, resulting in failure of solder joints, which seriously affects the service life and reliability of the product. For example, in the field of aerospace, when an aircraft is flying at high altitude, it will face extreme temperature changes, high humidity and corrosive gases in the atmosphere. If solder with poor corrosion resistance is used, the solder joints are easily corroded, which will endanger flight safety. In automobile manufacturing, automobile parts are exposed to outdoor environments for a long time and are eroded by rain, salt, dust, etc. The parts connected by ordinary solders are prone to rust and corrosion, which reduces the strength and performance of parts and increases maintenance costs. In terms of strength, the strength of traditional solders often cannot meet some applications with high requirements for structural strength. For example, in mechanical engineering, the connection of key components of large-scale mechanical equipment needs to withstand huge loads and stresses. If the solder strength is insufficient, the solder joints are prone to breakage under long-term mechanical stress, resulting in equipment failure and affecting production efficiency.
[0004] In order to improve the corrosion resistance of solder, some corrosion-resistant elements are usually added to the solder, but the addition of these elements often has a negative impact on other properties of the solder, such as reducing the wettability and fluidity of the solder, affecting the soldering quality. And methods to improve the strength of the solder, such as changing the alloy composition or performing heat treatment, may also bring problems such as increased costs and reduced toughness.
[0005] The Chinese invention patent with application number CN202411448985.4 discloses a high-strength and high-elongation SnPbSbInAu alloy solder and its preparation method. The alloy solder is composed of: Pb 33.0-36.5wt%, Sb 2.0-4.0wt%, In1.5-3.5wt%, Au 2.0-3.5wt%, P 0.005-0.012wt%, and the balance is Sn. The solder has a solid-liquid phase temperature of 180℃-185℃ and has the advantages of high elongation, high strength, high creep resistance, and excellent low-temperature service performance. However, its corrosion resistance is insufficient and it contains lead (Pb), which does not meet the current environmental protection and health requirements. Its high cost, complex preparation process, environmental and health issues and other defects limit its wide application.
[0006] The Chinese invention patent with application number CN202411527146.1 discloses an Ag-Cu-Ti-Zr-B active composite solder and its preparation method. The active composite solder is composed of the following mass percentage components: 5-8% Ti, 2-5% Zr, 0.1-2% B, and the balance is Ag-28Cu eutectic composition. The active composite solder has many advantages such as improved wettability, enhanced interface bonding strength, refined joint structure, and reduced brazing temperature. However, its thermal stability is insufficient, and its wettability and fluidity still need to be further improved. Wettability and fluidity directly affect the mechanical strength and corrosion resistance of the welded joint.
[0007] In summary, developing a solder with high welding strength and high corrosion resistance has become an urgent problem to be solved. Summary of the invention
[0008] In order to solve the above problems, the present invention provides a high-corrosion-resistant and high-strength solder and a preparation method thereof, wherein the solder improves the strength, corrosion resistance and stability of the welded joint by the cooperation of the solder and the flux. The preparation method adopts a structural design in which the solder wraps the flux, ensuring that the flux is evenly released during the welding process, improving the welding quality and achieving precise welding control.
[0009] The technical solution adopted by the present invention to achieve the above-mentioned purpose is: A high-corrosion-resistant and high-strength solder, comprising a solder and a brazing agent, wherein the solder comprises the following raw materials by weight: 40-55 parts of aluminum, 12-16 parts of aluminum silicon alloy, 27-33 parts of copper, 0.5-5 parts of germanium, 0.6-1 parts of manganese, 0.2-0.6 parts of titanium, 2-5 parts of tin, and 0.1-0.5 parts of rare earth elements; The brazing flux comprises the following raw materials by weight: 25-50 parts of potassium chloride, 10-35 parts of sodium chloride, 4.0-30.0 parts of lithium chloride, 10-20 parts of potassium fluoride-aluminum fluoride complex, 0.5-6 parts of zinc chloride, 2-6 parts of zinc fluoride, 0.05-3 parts of sodium fluoride, 0.05-3 parts of lithium fluoride, 0.05-2 parts of potassium hexafluorosilicate and 0.05-1.5 parts of potassium hydrogen fluoride.
[0010] The above-mentioned high corrosion resistance and high strength solder has significant performance advantages. Its raw material components improve welding strength, corrosion resistance and other comprehensive welding properties through synergistic effects. The combination of main components such as aluminum, aluminum silicon alloy and copper in the solder provides good mechanical properties. The addition of aluminum silicon alloy reduces the melting point of the solder and improves its thermal cracking resistance and wettability. The addition of copper significantly improves the strength of the solder. The addition of manganese further optimizes the microstructure of the solder and improves its tensile strength. The addition of trace elements such as germanium and titanium further optimizes the microstructure of the solder, improves its fluidity and wettability, enables it to better fill the weld during the welding process, and further improves the tensile strength, hardness and corrosion resistance of the weld. The addition of rare earth elements (such as lanthanum or cerium) significantly improves the corrosion resistance of the solder. Rare earth elements can form a dense oxide film on the surface of the solder to effectively block the corrosive medium. The addition of tin further improves the corrosion resistance of the solder, improves the fluidity and wettability of the solder, and maintains good strength.
[0011] Among the above-mentioned fluxes, chlorides such as potassium chloride, sodium chloride, and lithium chloride are basic components with low melting points and good fluidity. They can effectively remove the oxide film on the surface of the base material and the solder. At the same time, they form a thin liquid layer during the welding process, covering the metal surface to prevent further oxidation. Fluorides have strong film removal ability and can dissolve metal oxides, especially the oxide film of metals such as aluminum and magnesium. The addition of lithium chloride (LiCl) and lithium fluoride (LiF) can adjust the melting point of the flux. Zinc fluoride (ZnF2) and zinc chloride (ZnCl2) can reduce the melting temperature of the flux and provide good wettability and fluidity. These components can promote the flow and spreading of the solder, which helps the solder to better fill the weld during the welding process. Potassium hexafluorosilicate (K2SiF6) and potassium hydrogen fluoride (KHF2) can form a dense protective layer during the welding process to prevent corrosion of the welded joint. Sodium fluoride (NaF) and lithium fluoride (LiF) not only have a film-removing effect, but can also form stable compounds during the welding process, further improving the corrosion resistance of the welded joint.
[0012] By properly proportioning chloride and fluoride, the flux can melt and cover the welding surface at a lower temperature, reduce the oxidation of the base material, and improve the wettability and spreadability of the solder. The fluoride and chloride in the flux can reduce the interfacial tension of the liquid solder, promote the bonding between the solder and the base material, and thus improve the strength of the welded joint. The protective layer formed by fluoride and chloride can effectively prevent corrosion of the welded joint. Through the synergistic effect of each component, the above-mentioned flux can better remove the oxide film and optimize the wettability of the solder, thereby improving the strength of the welded joint.
[0013] Preferably, the potassium fluoride-aluminum fluoride composite comprises the following raw materials in parts by weight: 35-45 parts of potassium fluoride, 35-45 parts of aluminum fluoride, 5-8 parts of dopant, and 10-15 parts of coating material.
[0014] Preferably, the dopant is one or more of magnesium fluoride, cerium trifluoride, and lanthanum fluoride.
[0015] Preferably, the coating material is one or more of aluminum fluoride, lithium fluoride, and magnesium fluoride.
[0016] Preferably, the rare earth element is one or both of lanthanum and cerium.
[0017] Preferably, the preparation method of the potassium fluoride-aluminum fluoride complex is as follows: S1, dry-milling potassium fluoride and aluminum fluoride, with a ball-to-material ratio of 10-15:1, a ball-milling time of 1-2 hours, and a rotation speed of 300-400 rpm to mix them evenly; S2, adding the dopant to the mixed material in step S1, adding anhydrous ethanol as a dispersant, grinding for 30-60 minutes to make the dopant evenly distributed, the amount of anhydrous ethanol used is 10%-20% of the total mass of the dopant and the mixed material in step S1; S3, sintering the mixture ground in step S2 at a temperature of 600-800° C., keeping the temperature for 2-3 hours under an argon protective atmosphere, and then naturally cooling to room temperature, taking out the sintered material, washing it with deionized water to remove surface impurities, and then drying it at a temperature of 70-90° C. for 10-14 hours to obtain a composite 1; S4, adding the coating material to deionized water, stirring evenly to form a suspension, mixing the composite 1 with the suspension to obtain a slurry with a solid content of 20-40%, atomizing the slurry into small droplets, and then drying it with hot air, the hot air inlet temperature is 150-250° C., the air outlet temperature is 100-150° C., and the deionized water is evaporated to obtain dry coated composite particles; S5, subjecting the dried coated composite particles to high temperature treatment in an inert gas atmosphere at a temperature of 300-500° C. for a time of 1.5-3 hours.
[0018] The composite formed by potassium fluoride (KF) and aluminum fluoride (AlF3) has a lower melting temperature and better fluidity than single potassium fluoride or aluminum fluoride, which allows the welding process to be carried out at a lower temperature, which not only reduces energy consumption, but also reduces the thermal damage to the base material during welding. After melting, it forms a low-viscosity molten salt. The good fluidity enables the composite to better wet the base material surface during welding and cover the welding surface more evenly, thereby improving the welding quality. The composite of potassium fluoride and aluminum fluoride can effectively remove the oxide film on the surface of the base material at high temperature, especially when welding aluminum and its alloys. This composite can quickly dissolve the aluminum oxide layer and promote the good bonding between the brazing material and the base material. The addition of dopants (such as magnesium fluoride, cerium trifluoride, lanthanum fluoride) and rare earth elements (such as lanthanum, cerium) can significantly improve the performance of potassium fluoride and aluminum fluoride composites in removing oxide films and improving the performance of welded joints: the fluoride in the dopant can effectively remove the oxide film on the metal surface during welding. Rare earth elements such as lanthanum and cerium have good adsorption properties and can combine with oxides to form more stable compounds, thereby promoting the removal of oxide films. Rare earth elements can also improve the tensile strength and toughness of welded joints by changing the microstructure of weld metal. Fluorides in dopants can not only remove oxide films during welding, but also improve the wettability and formability of welds and improve the bonding ability between metals and fluxes. In addition, fluorides can also enhance the mechanical properties of welding materials by forming stable fluoride ion bridge structures. Components such as lithium fluoride in coating materials can reduce the melting point of the composite and improve its fluidity. The coating layer can improve the surface properties of the composite, so that it has better wettability and fluidity during welding. Moreover, the composite has more stable performance after coating treatment, and can better play the role of film removal, wetting and gap filling during welding. The coating layer forms an effective protective layer, which also improves its corrosion resistance. Furthermore, the coating material is subjected to high temperature treatment in an inert gas atmosphere. The inert atmosphere heat treatment can maintain the integrity and characteristics of the material at high temperatures and prevent oxidation. At the same time, its surface properties will be significantly improved, which helps to improve the thermal stability, mechanical properties and corrosion resistance of the material.
[0019] The method for preparing the above-mentioned high corrosion resistance and high strength solder comprises the following steps: Step 1, melting the brazing material at 700-800° C. for 30-80 minutes; Step 2, casting, cooling, and rolling the smelted solder alloy into a strip, and then processing the strip solder into a U-shaped groove; Step 3, mixing and crushing the flux raw materials evenly by ball milling to obtain flux powder with a particle size of 20-30 μm; Step 4, pouring the flux powder into the U-shaped groove of the strip solder, and then closing the U-shaped groove of the strip solder by rolling.
[0020] Preferably, the thickness of the strip solder in step 2 is 0.5-1 mm.
[0021] Preferably, in step 3, the ball-to-material ratio during ball milling is 15-20:1 and the rotation speed is 350-450 r / min.
[0022] Preferably, the high corrosion resistance and high strength solder obtained in step 4 is stretched into a filament with a diameter of 0.3-0.6 mm.
[0023] The present invention has the following beneficial effects: The solder of the present invention provides good basic strength through the reasonable proportion of metals such as aluminum and copper, and the addition of elements such as titanium and manganese helps to refine the grains and further improve the strength. Aluminum itself has a certain corrosion resistance, and the addition of germanium can enhance its corrosion resistance in a specific environment. Rare earth elements can also improve the properties of the surface oxide film and improve corrosion resistance. The reasonable combination of each component makes the solder have good wettability and fluidity, which is convenient for welding operation, and the synergistic effect of each raw material component significantly improves welding strength, corrosion resistance and other comprehensive welding properties, and is suitable for high-performance welding requirements. The flux of the present invention achieves good comprehensive performance in terms of deoxidation ability, thermal stability, corrosion resistance, welding strength, etc. by reasonably proportioning various chlorides and fluorides and utilizing their synergistic effect. It can effectively remove oxides on the metal surface, form a high-strength weld, and also improve corrosion resistance. The solder and flux of the present invention cooperate with each other to jointly improve the comprehensive strength and stability of the welded joint.
[0024] Furthermore, the application of the potassium fluoride-aluminum fluoride composite in the flux of the present invention has significant advantages. Compared with a single potassium fluoride and aluminum fluoride mixture, the composite can significantly reduce the melting temperature, improve the stability and reliability of the welding process, and has good effects in improving wettability, fluidity, film removal ability and welding joint quality. The addition of dopants (such as magnesium fluoride, cerium trifluoride, and lanthanum fluoride) further enhances the chemical activity of the composite, making it better in removing oxide films. Rare earth elements (such as lanthanum and cerium) further optimize the performance of the welded joint, improving its corrosion resistance and strength. The potassium fluoride-aluminum fluoride composite has high thermal stability and can maintain good chemical properties at high temperatures. This makes the composite not easy to decompose during the welding process, thereby ensuring the stability and reliability of the welding process. High-temperature treatment in an inert gas environment helps to further improve the thermal stability and mechanical properties of the material. High-temperature treatment of the coated material in an inert gas atmosphere improves material properties, protects material integrity, optimizes surface characteristics, and improves thermal stability and mechanical properties.
[0025] The preparation method of the present invention adopts a structural design of brazing material wrapping flux, which ensures uniform distribution and precise control of the brazing material and flux, ensures uniform release of the flux during welding, improves welding quality, and is stretched into a filamentous structure for easy welding operation, while further realizing precise welding control. The preparation method ensures the stability and consistency of product quality, is easy to operate, and is suitable for mass production. DETAILED DESCRIPTION
[0026] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0027] The raw materials used in the following examples are all common commercial products. Among them, the brazing material raw materials are aluminum ingots, purity 99.85%; aluminum silicon alloy is aluminum silicon 20, Shanghai Qichen Industrial Co., Ltd.; copper, purity 99.97%; germanium is 1-15mm germanium particles, purity 99.9%; manganese is manganese flakes, content 99.7%; titanium, purity 99.99%; tin, purity 99.99%; lanthanum, purity 99.9%; cerium, purity 99.9%; potassium chloride, white powder with mesh number 90, Sichuan Xinyun Jinhong Technology Co., Ltd.; sodium chloride, crystalline particles, 50 mesh, Henan Tuohong Chemical Co., Ltd.; lithium chloride, effective ingredient content 99%, white crystals, Jinan Yunuo Chemical Co., Ltd.; zinc chloride, white crystalline powder, purity 98%, Sichuan Chengzhu Biotechnology Co., Ltd.; zinc fluoride, white powder , purity 99%; sodium fluoride, white crystalline powder, purity 99%; lithium fluoride, white powder, purity 99%; potassium hexafluorosilicate (K2SiF6) white crystalline powder, purity 99%; potassium hydrogen fluoride, white crystalline powder, purity 99%; potassium fluoride white crystalline powder, purity 99%, Shandong Yuxuan Chemical Products Co., Ltd.; aluminum fluoride, purity 99%, white crystalline powder, Langfang Qianyao Technology Co., Ltd.; magnesium fluoride, colorless crystals or white powder, purity 99%, Langfang Qianyao Technology Co., Ltd.; cerium trifluoride, 300 mesh powder, active ingredient content 99.99%, Shandong Desheng New Materials Co., Ltd.; lanthanum fluoride (LaF3), white crystalline powder, purity 99%, Shandong Haoyao New Materials Co., Ltd. Example 1
[0028] A high-corrosion-resistant and high-strength solder comprises a solder and a brazing agent. The solder comprises the following raw materials by weight: 50 parts of aluminum, 14 parts of aluminum silicon alloy, 30 parts of copper, 3 parts of germanium, 0.8 parts of manganese, 0.4 parts of titanium, 3 parts of tin, 0.15 parts of lanthanum and 0.15 parts of cerium.
[0029] The flux comprises the following raw materials by weight: 40 parts of potassium chloride, 26 parts of sodium chloride, 20 parts of lithium chloride, 14 parts of potassium fluoride-aluminum fluoride complex, 3 parts of zinc chloride, 5 parts of zinc fluoride, 2 parts of sodium fluoride, 2 parts of lithium fluoride, 1 part of potassium hexafluorosilicate (K2SiF6), and 0.8 parts of potassium hydrogen fluoride (KHF2).
[0030] The potassium fluoride-aluminum fluoride composite comprises the following raw materials in parts by weight: 40 parts of potassium fluoride, 40 parts of aluminum fluoride, 6 parts of dopants, and 12 parts of coating materials, wherein the dopants are magnesium fluoride, cerium trifluoride, and lanthanum fluoride (LaF3), and the weight ratio is 1:1.2:1, and the coating materials are lithium fluoride and magnesium fluoride, and the weight ratio is 1:1.
[0031] The preparation method of the potassium fluoride-aluminum fluoride complex is as follows: S1, put potassium fluoride and aluminum fluoride into a ball mill for dry ball milling, with a ball-to-material ratio of 12:1, a ball milling time of 1.8 h, and a rotation speed of 350 rpm to mix them evenly; S2, adding the dopant to the mixed material in step S1, adding anhydrous ethanol as a dispersant, grinding for 45 minutes to make the dopant evenly distributed, the amount of anhydrous ethanol used is 15% of the total mass of the dopant and the mixed material in step S1; S3, putting the mixture ground in step S2 into a crucible, placing it in a tube furnace for sintering, heating it to 700°C at a heating rate of 5°C / min, keeping it warm for 2.5 hours under an argon protective atmosphere, and then naturally cooling it to room temperature, taking out the sintered material, washing it with deionized water to remove surface impurities, and then drying it at a temperature of 82°C for 11 hours to obtain a composite 1; S4, adding the coating material to deionized water, stirring evenly to form a uniform suspension, mixing the composite 1 with the suspension to obtain a slurry with a solid content of 30%, atomizing the slurry into tiny droplets through the nozzle of a spray drying device, spraying the droplets into a drying chamber for drying, and introducing hot air into the drying chamber, with an inlet air temperature of 200° C. and an outlet air temperature of 120° C. After the hot air contacts the droplets, the deionized water evaporates rapidly to form dry coated composite particles, and the dried coated composite particles are separated from the air flow by a cyclone separator and collected; S5, subjecting the dried coated composite particles to high temperature treatment in an inert gas atmosphere at a temperature of 450° C. for 2.5 hours.
[0032] The method for preparing the above-mentioned high corrosion resistance and high strength solder comprises the following steps: Step 1, melting the brazing material at 750° C. for 50 min; Step 2, casting, cooling, and rolling the smelted solder alloy into a strip with a thickness of 0.7 mm, and then processing the strip solder into a U-shaped groove; Step 3, mixing and crushing the flux raw materials by ball milling to obtain flux powder with a particle size of 25 μm, wherein the ball-to-material ratio during the ball milling process is 20:1 and the rotation speed is 400 r / min; Step 4, pour the flux powder into the U-shaped groove, then close the U-shaped groove of the strip solder by rolling, and then stretch it into a filament with a diameter of 0.5 mm. Example 2
[0033] A high-corrosion-resistant and high-strength solder comprises a solder and a brazing agent. The solder comprises the following raw materials by weight: 40 parts of aluminum, 16 parts of aluminum silicon alloy, 33 parts of copper, 5 parts of germanium, 1 part of manganese, 0.5 parts of titanium, 2 parts of tin, 0.06 parts of lanthanum, and 0.04 parts of cerium.
[0034] The flux comprises the following raw materials by weight: 25 parts of potassium chloride, 35 parts of sodium chloride, 4 parts of lithium chloride, 17 parts of potassium fluoride-aluminum fluoride complex, 0.5 parts of zinc chloride, 4 parts of zinc fluoride, 0.05 parts of sodium fluoride, 3 parts of lithium fluoride, 0.05-2 parts of potassium hexafluorosilicate, and 0.05 parts of potassium hydrogen fluoride.
[0035] The potassium fluoride-aluminum fluoride composite comprises the following raw materials in parts by weight: 45 parts of potassium fluoride, 35 parts of aluminum fluoride, 5 parts of dopant, and 10 parts of coating material, wherein the dopant is magnesium fluoride, cerium trifluoride, and lanthanum fluoride (LaF3), and the weight ratio is 1:1.5:2; the coating material is lithium fluoride and magnesium fluoride, and the weight ratio is 1:2.
[0036] The preparation method of the potassium fluoride-aluminum fluoride complex is as follows: S1, put potassium fluoride and aluminum fluoride into a ball mill for dry ball milling, with a ball-to-material ratio of 10:1, a ball milling time of 1.5 h, and a rotation speed of 400 rpm to mix them evenly; S2, adding the dopant to the mixed material in step S1, adding anhydrous ethanol as a dispersant, grinding for 30 minutes to make the dopant evenly distributed, the amount of anhydrous ethanol used is 10% of the total mass of the dopant and the mixed material in step S1; S3, putting the mixture ground in step S2 into a crucible, placing it in a tube furnace for sintering, heating it to 600°C at a heating rate of 5°C / min, keeping it warm for 3 hours under an argon protective atmosphere, and then naturally cooling it to room temperature, taking out the sintered material, washing it with deionized water to remove surface impurities, and then drying it at a temperature of 80°C for 12 hours to obtain a composite 1; S4, adding the coating material to deionized water, stirring evenly to form a uniform suspension, mixing the composite 1 with the suspension to obtain a slurry with a solid content of 20%, atomizing the slurry into tiny droplets through the nozzle of a spray drying device, spraying the droplets into a drying chamber for drying, and introducing hot air into the drying chamber, with an inlet air temperature of 150° C. and an outlet air temperature of 100° C. After the hot air contacts the droplets, the deionized water evaporates rapidly to form dry coated composite particles, and the dried coated composite particles are separated from the air flow by a cyclone separator and collected; S5, subjecting the dried coated composite particles to high temperature treatment in an inert gas atmosphere at a temperature of 400° C. for 2 hours.
[0037] The method for preparing the above-mentioned high corrosion resistance and high strength solder comprises the following steps: Step 1, melting the brazing material at 800° C. for 40 minutes; Step 2, casting, cooling, and rolling the smelted solder alloy into a strip with a thickness of 0.8 mm, and then processing the strip solder into a U-shaped groove; Step 3, mixing and crushing the flux raw materials by ball milling to obtain flux powder with a particle size of 20 μm, wherein the ball-to-material ratio during the ball milling process is 18:1 and the rotation speed is 350 r / min; Step 4, pour the flux powder into the U-shaped groove, then close the U-shaped groove of the strip solder by rolling, and then stretch it into a filament with a diameter of 0.4 mm. Example 3
[0038] A high-corrosion-resistant and high-strength solder comprises a solder and a brazing agent. The solder comprises the following raw materials by weight: 55 parts of aluminum, 12 parts of aluminum silicon alloy, 27 parts of copper, 0.5 parts of germanium, 0.6 parts of manganese, 0.2 parts of titanium, 4 parts of tin, 0.4 parts of lanthanum and 0.1 parts of cerium.
[0039] The brazing flux comprises the following raw materials by weight: 50 parts of potassium chloride, 10 parts of sodium chloride, 30 parts of lithium chloride, 10 parts of potassium fluoride-aluminum fluoride complex, 6 parts of zinc chloride, 2 parts of zinc fluoride, 3 parts of sodium fluoride, 1 part of lithium fluoride, 0.05-2 parts of potassium hexafluorosilicate and 1.5 parts of potassium hydrogen fluoride.
[0040] The potassium fluoride-aluminum fluoride composite comprises the following raw materials in parts by weight: 35 parts of potassium fluoride, 45 parts of aluminum fluoride, 8 parts of dopant, and 15 parts of coating material, wherein the dopant is magnesium fluoride, cerium trifluoride, and lanthanum fluoride (LaF3), and the weight ratio is 1:2:1; the coating material is lithium fluoride and magnesium fluoride, and the weight ratio is 1:0.5.
[0041] The preparation method of the potassium fluoride-aluminum fluoride complex is as follows: S1, put potassium fluoride and aluminum fluoride into a ball mill for dry ball milling, with a ball-to-material ratio of 15:1, a ball milling time of 2 h, and a rotation speed of 300 rpm to mix them evenly; S2, adding the dopant to the mixed material in step S1, adding anhydrous ethanol as a dispersant, grinding for 60 minutes to make the dopant evenly distributed, the amount of anhydrous ethanol used is 20% of the total mass of the dopant and the mixed material in step S1; S3, putting the mixture ground in step S2 into a crucible, placing it in a tube furnace for sintering, heating it to 800°C at a heating rate of 5°C / min, keeping it warm for 2 hours under an argon protective atmosphere, and then naturally cooling it to room temperature, taking out the sintered material, washing it with deionized water to remove surface impurities, and then drying it at a temperature of 90°C for 10 hours to obtain a composite 1; S4, adding the coating material to deionized water, stirring evenly to form a uniform suspension, mixing the composite 1 with the suspension to obtain a slurry with a solid content of 40%, atomizing the slurry into tiny droplets through the nozzle of a spray drying device, spraying the droplets into a drying chamber for drying, and introducing hot air into the drying chamber, with an inlet air temperature of 250°C and an outlet air temperature of 150°C. After the hot air contacts the droplets, the deionized water evaporates rapidly to form dry coated composite particles, and the dried coated composite particles are separated from the air flow by a bag filter and collected; S5, subjecting the dried coated composite particles to high temperature treatment in an inert gas atmosphere at a temperature of 500° C. for 1.5 h.
[0042] The method for preparing the above-mentioned high corrosion resistance and high strength solder comprises the following steps: Step 1, melting the brazing material at 700° C. for 80 minutes; Step 2, casting, cooling, and rolling the smelted solder alloy into a strip with a thickness of 1 mm, and then processing the strip solder into a U-shaped groove; Step 3, mixing and crushing the flux raw materials by ball milling to obtain flux powder with a particle size of 30 μm, wherein the ball-to-material ratio during the ball milling process is 20:1 and the rotation speed is 450 r / min; Step 4, pour the flux powder into the U-shaped groove, then close the U-shaped groove of the strip solder by rolling, and then stretch it into a filament with a diameter of 0.6 mm. Example 4
[0043] A high-corrosion-resistant and high-strength solder comprises a solder and a brazing agent. The solder comprises the following raw materials by weight: 48 parts of aluminum, 13 parts of aluminum silicon alloy, 31 parts of copper, 2 parts of germanium, 0.9 parts of manganese, 0.6 parts of titanium, 5 parts of tin, 0.1 parts of lanthanum, and 0.3 parts of cerium.
[0044] The brazing flux comprises the following raw materials by weight: 45 parts of potassium chloride, 20 parts of sodium chloride, 18 parts of lithium chloride, 20 parts of potassium fluoride-aluminum fluoride complex, 4 parts of zinc chloride, 6 parts of zinc fluoride, 2.5 parts of sodium fluoride, 0.05 parts of lithium fluoride, 0.05-2 parts of potassium hexafluorosilicate, and 1.2 parts of potassium hydrogen fluoride.
[0045] The potassium fluoride-aluminum fluoride composite comprises the following raw materials in parts by weight: 38 parts of potassium fluoride, 42 parts of aluminum fluoride, 7 parts of dopant, and 14 parts of coating material, wherein the dopant is magnesium fluoride, cerium trifluoride, and lanthanum fluoride (LaF3), and the weight ratio is 1:1.5:1.5, and the coating material is lithium fluoride and magnesium fluoride, and the weight ratio is 1:1.5.
[0046] The preparation method of the potassium fluoride-aluminum fluoride complex is as follows: S1, put potassium fluoride and aluminum fluoride into a ball mill for dry ball milling, with a ball-to-material ratio of 14:1, a ball milling time of 1 h, and a rotation speed of 350 rpm to mix them evenly; S2, adding the dopant to the mixed material in step S1, adding anhydrous ethanol as a dispersant, grinding for 50 minutes to make the dopant evenly distributed, the amount of anhydrous ethanol used is 18% of the total mass of the dopant and the mixed material in step S1; S3, putting the mixture ground in step S2 into a crucible, placing it in a tube furnace for sintering, heating it to 650°C at a heating rate of 5°C / min, keeping it warm for 2.5 hours under an argon protective atmosphere, and then naturally cooling it to room temperature, taking out the sintered material, washing it with deionized water to remove surface impurities, and then drying it at 70°C for 14 hours to obtain a composite 1; S4, adding the coating material to deionized water, stirring evenly to form a uniform suspension, mixing the composite 1 with the suspension to obtain a slurry with a solid content of 35%, atomizing the slurry into tiny droplets through the nozzle of a spray drying device, spraying the droplets into a drying chamber for drying, and introducing hot air into the drying chamber, with an inlet air temperature of 180° C. and an outlet air temperature of 120° C. After the hot air contacts the droplets, the deionized water evaporates rapidly to form dry coated composite particles, and the dried coated composite particles are separated from the air flow by a cyclone separator and collected; S5, subjecting the dried coated composite particles to high temperature treatment in an inert gas atmosphere at a temperature of 300° C. for 3 hours.
[0047] The method for preparing the above-mentioned high corrosion resistance and high strength solder comprises the following steps: Step 1, melting the brazing material at 800° C. for 30 minutes; Step 2, casting, cooling, and rolling the smelted solder alloy into a strip with a thickness of 0.5 mm, and then processing the strip solder into a U-shaped groove; Step 3, mixing and crushing the flux raw materials by ball milling to obtain flux powder with a particle size of 28 μm, wherein the ball-to-material ratio during the ball milling process is 15:1 and the rotation speed is 400 r / min; Step 4, pour the flux powder into the U-shaped groove, then close the U-shaped groove of the strip solder by rolling, and then stretch it into a filament with a diameter of 0.3 mm.
[0048] Comparative Example 1 A high-corrosion-resistant and high-strength solder comprises a solder and a brazing agent. The solder comprises the following raw materials by weight: 50 parts of aluminum, 14 parts of aluminum silicon alloy, 30 parts of copper, 3 parts of germanium, 0.8 parts of manganese, 0.4 parts of titanium, and 3 parts of tin.
[0049] The flux comprises the following raw materials by weight: 40 parts of potassium chloride, 26 parts of sodium chloride, 20 parts of lithium chloride, 3 parts of zinc chloride, 5 parts of zinc fluoride, 2 parts of sodium fluoride and 2 parts of lithium fluoride.
[0050] The rest is the same as in Example 1.
[0051] Comparative Example 2 A high-corrosion-resistant and high-strength solder comprises a solder and a brazing agent. The solder comprises the following raw materials by weight: 50 parts of aluminum, 14 parts of aluminum silicon alloy, 30 parts of copper, 3 parts of germanium, 0.8 parts of manganese, 0.4 parts of titanium, 3 parts of tin, 0.15 parts of lanthanum and 0.15 parts of cerium.
[0052] The brazing flux comprises the following raw materials by weight: 40 parts of potassium chloride, 26 parts of sodium chloride, 20 parts of lithium chloride, 7 parts of potassium fluoride, 7 parts of aluminum fluoride, 3 parts of zinc chloride, 5 parts of zinc fluoride, 2 parts of sodium fluoride, 2 parts of lithium fluoride, 1 part of potassium hexafluorosilicate, and 0.8 parts of potassium hydrogen fluoride.
[0053] The rest is the same as in Example 1.
[0054] Performance Testing The aluminum alloy pipes were welded using the solders of Examples 1-4 and Comparative Examples 1 and 2, and the corrosion resistance of the welded joints was tested according to GB / T 10125-2021 "Artificial atmosphere corrosion test-salt spray test", specifically a neutral salt spray test with a test cycle of 96 hours; the tensile strength and shear strength of the welded joints were tested according to GB / T228.1-2010 and GB / T 11363-2008. The results are shown in Table 1.
[0055] Table 1. Welding performance test results
[0056] It can be seen from Table 1 that the corrosion resistance of the solder and the mechanical properties of the welded joints of Examples 1-4 of the present invention are better than those of Comparative Examples 1 and 2.
[0057] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0058] Although the embodiments of the present application have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present application, and that the scope of the present application is defined by the appended claims and their equivalents.
Claims
1. A high corrosion resistance and high strength solder, characterized in that: The brazing material comprises a brazing material and a brazing agent, wherein the brazing material comprises the following raw materials by weight: 40-55 parts of aluminum, 12-16 parts of aluminum silicon alloy, 27-33 parts of copper, 0.5-5 parts of germanium, 0.6-1 parts of manganese, 0.2-0.6 parts of titanium, 2-5 parts of tin, and 0.1-0.5 parts of rare earth elements; The brazing flux comprises the following raw materials by weight: 25-50 parts of potassium chloride, 10-35 parts of sodium chloride, 4.0-30.0 parts of lithium chloride, 10-20 parts of potassium fluoride-aluminum fluoride complex, 0.5-6 parts of zinc chloride, 2-6 parts of zinc fluoride, 0.05-3 parts of sodium fluoride, 0.05-3 parts of lithium fluoride, 0.05-2 parts of potassium hexafluorosilicate and 0.05-1.5 parts of potassium hydrogen fluoride.
2. The high corrosion resistance and high strength solder according to claim 1, characterized in that: The potassium fluoride-aluminum fluoride composite comprises the following raw materials in parts by weight: 35-45 parts of potassium fluoride, 35-45 parts of aluminum fluoride, 5-8 parts of dopant, and 10-15 parts of coating material.
3. The high corrosion resistance and high strength solder according to claim 2, characterized in that: The dopant is one or more of magnesium fluoride, cerium trifluoride and lanthanum fluoride.
4. The high corrosion resistance and high strength solder according to claim 2, characterized in that: The coating material is one or more of aluminum fluoride, lithium fluoride and magnesium fluoride.
5. The high corrosion resistance and high strength solder according to claim 1, characterized in that: The rare earth element is one or both of lanthanum and cerium.
6. The high corrosion resistance and high strength solder according to claim 2, characterized in that: The preparation method of the potassium fluoride-aluminum fluoride complex is as follows: S1, dry-milling potassium fluoride and aluminum fluoride, with a ball-to-material ratio of 10-15:1, a ball-milling time of 1-2 hours, and a rotation speed of 300-400 rpm to mix them evenly; S2, adding the dopant to the mixed material in step S1, adding anhydrous ethanol as a dispersant, grinding for 30-60 minutes to make the dopant evenly distributed, the amount of anhydrous ethanol used is 10%-20% of the total mass of the dopant and the mixed material in step S1; S3, sintering the mixture ground in step S2 at a temperature of 600-800° C., keeping the temperature for 2-3 hours under an argon protective atmosphere, and then naturally cooling to room temperature, taking out the sintered material, washing it with deionized water to remove surface impurities, and then drying it at a temperature of 70-90° C. for 10-14 hours to obtain a composite 1; S4, adding the coating material to deionized water, stirring evenly to form a suspension, mixing the composite 1 with the suspension to obtain a slurry with a solid content of 20-40%, atomizing the slurry, and then drying it with hot air, the hot air inlet temperature is 150-250° C., the air outlet temperature is 100-150° C., and the deionized water is evaporated to obtain dry coated composite particles; S5, subjecting the dried coated composite particles to high temperature treatment in an inert gas atmosphere at a temperature of 300-500° C. for a time of 1.5-3 hours.
7. The method for preparing the high corrosion resistance and high strength solder according to any one of claims 1 to 6, characterized in that: The following steps are involved: Step 1, melting the brazing material at 700-800° C. for 30-80 minutes; Step 2, casting, cooling, and rolling the smelted solder alloy into a strip, and then processing the strip solder into a U-shaped groove; Step 3, mixing and crushing the flux raw materials by ball milling to obtain flux powder with a particle size of 20-30 μm; Step 4, pouring flux powder into the U-shaped groove of the strip solder, and then closing the U-shaped groove of the strip solder by rolling.
8. The method for preparing the high corrosion resistance and high strength solder according to claim 7, characterized in that: The thickness of the strip solder in step 2 is 0.5-1 mm.
9. The method for preparing the high corrosion resistance and high strength solder according to claim 7, characterized in that: In step 3, the ball-to-material ratio during ball milling is 15-20:1 and the rotation speed is 350-450 r / min.
10. The method for preparing the high corrosion resistance and high strength solder according to claim 7, characterized in that: The high corrosion resistance and high strength solder obtained in step 4 is stretched into a filament with a diameter of 0.3-0.6 mm.
Citation Information
Patent Citations
High-strength high-elongation SnPbSbInAu alloy solder and preparation method thereof
CN119260236A
Ag-Cu-Ti-Zr-B active composite brazing filler metal and application thereof
CN119328363A
Intermediate-temperature aluminum-based aluminum alloy solder paste and preparation method thereof
CN102303201A
Al-Si-Cu-Zn-Sn-Ni aluminum-based brazing filler metal and preparation method thereof
CN102319963A
Aluminum-silicon alloy seamless flux-cored wire for brazing as well as preparation and application
CN103551757A